Properties of human blood monocytes. I. CD91 expression and log orthogonal light scatter provide a robust method to identify monocytes that is more accurate than CD14 expression. Issue 2 (8th October 2013) - Hudig, Dorothy; Hunter, Kenneth W.; Diamond, W. John; Redelman, Doug
<x xml:space="preserve">Abstract</x> Background This study was designed to improve identification of human blood monocytes by using antibodies to molecules that occur consistently on all stages of monocyte development and differentiation. Methods We examined blood samples from 200 healthy adults without clinically diagnosed immunological abnormalities by flow cytometry (FCM) with multiple combinations of antibodies and with a hematology analyzer (Beckman LH750). Results CD91 (α2‐macroglobulin receptor) was expressed only by monocytes and to a consistent level among subjects [mean median fluorescence intensity (MFI) = 16.2 ± 3.2]. Notably, only 85.7 ± 5.82% of the CD91+ monocytes expressed high levels of the classical monocyte marker CD14, with some CD91+ CD16+ cells having negligible CD14, indicating that substantial FCM under‐counts will occur when monocytes are identified by high CD14. CD33 (receptor for sialyl conjugates) was co‐expressed with CD91 on monocytes but CD33 expression varied by nearly ten‐fold among subjects (mean MFI = 17.4 ± 7.7). In comparison to FCM analyses, the hematology analyzer systematically over‐counted monocytes and eosinophils while lymphocyte and neutrophil differential values generally agreed with FCM methods. Conclusions CD91 is a better marker to identify monocytes than CD14 or CD33. Furthermore, FCM (with anti‐CD91) identifies monocytes better than a currently used clinical CBC instrument. Use of anti‐CD91 together with anti‐CD14 and anti‐CD16 supports the identification of the diagnostically significant monocyte populations with variable expression of CD14 and CD16. © 2013 International Clinical Cytometry Society